Project on Human Development in Chicago Neighborhoods (PHDCN): Conflict Tactics Scale for Partner and Spouse, Wave 1, 1994-1997 - Earls, Felton J. ([Verlag nicht ermittelbar], 2005)
The Project on Human Development in Chicago Neighborhoods (PHDCN) was a large-scale, interdisciplinary study of how families, schools, and neighborhoods affect child and adolescent development. One component of the PHDCN was the Longitudinal Cohort Study, which was a series of coordinated longitudinal studies that followed over 6,000 randomly selected children, adolescents, and young adults, and their primary caregivers over time to examine the changing circumstances of their lives, as well as the personal characteristics, that might lead them toward or away from a variety of antisocial behaviors. Numerous measures were administered to respondents to gauge various aspects of human development, including individual differences, as well as family, peer, and school influences. One such measure was the Conflict Tactics Scale for Partner and Spouse (CTSP). The CTSP was administered to either the primary caregiver (PC) of subjects belonging to Cohorts 0 to 15, or to the subjects of Cohort 18. It measured both the extent to which partners in a dating, cohabiting, or marital relationship engage in psychological and physical attacks on each other and also their use of reasoning or negotiation to deal with conflicts.